Crepuscular landscapes: rethinking human-coyote relations in situations involving fog in a Costa Rican rural community (Simbiótica. Revista Eletrônica, 2022)
This paper critically reflects on human-coyote interactions emerging from more-than-human entanglements in San Gerado de Oreamuno, localized in Cartago province (Costa Rica). Through a sensory perspective, I examine the role of fog in (re)configuring an “multinatural territory” that affects relations between many vitalities. I also provide some theoretical insights from multispecies ethnography and more-than-human geography to problematize human-nature dichotomy and begin to understand the affective atmospheres involved in both physical experiences and oral accounts of local people. Finally, I suggest that my own interests provide me of interesting lens to frame the meanings attributed to fog and its influence on the emergence of “proximity ecologies” that determine human-coyote relations in that community.Keywords: Anthropocene; Canis latrans; Affective ecologies; Human-animal interaction.